Profiling the types of restaurants that sell wild meat in Central African cities - Wright, J.H.; Malekani, D.; Funk, S.M.; Ntshila, J.; Mayet, L.; Mwinyihali, R.; Fa, J.E.; Wieland, M. (Wiley, 2022)
Central African cities are major centres of demand for wild meat, even when affordable alternative proteins are widely available. Many people eat wild meat in restaurants; therefore, restaurateurs are well placed to provide insights into the wild meat trade and consumer preferences. We surveyed 326 restaurants in Brazzaville and Kinshasa, the adjoining capital cities of the Republic of Congo and Democratic Republic of the Congo, to determine which types of restaurants sell wild meat, how sales of wild meat dishes compared with those containing other proteins, and the importance of wild meat to these businesses. The majority of wild meat-selling restaurants are informal establishments owned by women. Although most only sell wild meat dishes weekly, we estimate that nearly 10,000 wild meat dishes are consumed daily in restaurants across Brazzaville and Kinshasa. Its wide availability reinforces the social norm around eating wild meat, yet few restaurateurs considered wild meat to be central to the viability of their business. It is important to distinguish between restaurants reliant on wild meat sales and those that offer it to diversify their menus. Forging partnerships with restaurateurs offer untapped potential to develop mutually beneficial allegiances to further wild meat demand reduction efforts.